Linguistic and semantic complexity in problem posing by students, pre-service and service teachers in high school - Arellano García, Yuridia; Hernández Cruz, Lucero; Hernández Moreno, Antonia (IE Revista de Investigación Educativa de la REDIECH, 2021)
In this research we present an analysis about the linguistic and mathematical complexity of problem posing by 34 participants (10 high school students, 15 high school math pre-service teachers and 9 high school math service teachers) when facing a task of invention of a history-type arithmetic problem. Its syntactic linguistic complexity was analyzed using assignment, relational and conditional propositions, and its mathematical complexity through its underlying semantic structural relationships. We found that the invention of problems with high semantic and syntactic complexity is scarce, mainly in service teachers, who present a more organized scheme of problems, in contrast to pre-service teachers who propose a greater number of problems with a higher level of complexity but presenting a series of poorly organized problems. In the case of students, up to 75% of their proposals are of the least complexity, both syntactic and semantic. The similarity between the types of problems proposed by the three groups studied is highlighted. We also discussed about the advantages of proposing activities for the invention of problems in the upper-middle and upper-level classroom, mainly in teachers training.